Hydrological modeling of large river basins: how much is enough? - Johnston, Robyn M.; Smakhtin, Vladimir U. (Springer, 2014)
Hydrological modeling is an indispensable component of water resources research and management in large river basins. There is a tendency for each new group working in a basin to develop their own model, resulting in a plethora of such tools for each major basin. The question then becomes: how much modeling is enough? This study reviews hydrological modeling in four large basins (Nile, Mekong, Ganges and Indus). Based on this review, four areas for action to improve effectiveness and reduce duplication in hydrological modeling of large basins are suggested. Model setups and input data, as well as model results, should be published, to allow more coordinated approaches and capitalize on past modeling efforts. More focus is needed on reporting uncertainty, to allow more realistic assessment of the degree of confidence in using results for policy and management. Initiatives are needed to improve the quantity and quality of data for model input, calibration and validation, both traditional hydrological monitoring (improved networks, expansion of automated systems) and new methods for data collection (remote sensing, crowd-sourcing and community based observations). Finally, within each major basin, an appropriate agency should be identified and resourced to take responsibility for data sharing and coordination, to reduce redundancy of effort and promote collaboration.